Asymmetric development and function of paired sperm-storage organs in Drosophila melanogaster - Dawn S. Chen; Kianairy Marrero; Javier Arturo Sanchez-Lopez; Michael Belenky; Jonathon M. Thomalla; Norene A. Buehner; Ido Apel; Yarin Levi; Yassi Hafezi; Shuran Wang; Andrew G. Clark; Yael Heifetz; et al. (Proceedings of the National Academy of Sciences, 2025)
Paired structures often have similar forms and functions, but the processes underlying their formation can differ. They may originate from a common source or from parallel sources, or arise from distinct precursors that follow separate developmental pathways, ultimately converging on comparable structures and roles. When asymmetries emerge and persist through development, members of the pair can specialize in ways that might increase fitness. Here, we report that the Drosophila melanogaster female’s pair of spermathecae, which appear similar and have the common role of sperm storage, derive from different developmental compartments defined by expression of lineage-tracing markers corresponding, respectively, to the key patterning genes engrailed and wingless . We further find that the two spermathecae show significant differences in size, secretory activity, and calcium levels and, perhaps as a consequence, sperm retention dynamics. These results open broad avenues for understanding how developmental, physiological, and behavioral asymmetries arise and impact reproductive success.